Discursive practices instilling the peace values for foreign learners in the BIPA textbook - Roekhan, Roekhan; Suyitno, Imam; Andajani, Kusubakti; Martutik, Martutik (Jurnal Cakrawala Pendidikan, 2024)
Studies to inculcate new values for students, including foreign learners, are necessary, given the high incidence of injustice and bullying. The inculcation of these values in Indonesian language learning for foreign learners (BIPA) is closely related to the cultural learning of Indonesian people who love peace. This study aimed to reveal the discursive practice of embedding values in BIPA textbooks. The data sources were the BIPA textbook published in 2019 by the Indonesian Ministry of Education and Culture for advanced levels. This study used Critical Discourse Analysis (CDA) and Visual Grammar Theory (VGT) to analyze the data. This study found three categories of values related to self, social relations, and environment. Values about caring for society, the environment, and democracy dominated the BIPA textbook. The textbook ignored the discursive practice of instilling inner value. This finding significantly contributes to the authors of language textbooks for foreign learners to consider cultural values that lead to developing more comprehensive subject matter. In addition, these findings also make it clear that foreign language teachers do not teach their language but also need to emphasize learning about values that support students' communicative competence.